Shifting participatory approach when ideology meets reality: a grounded theory study based on project leaders’ experiences with peer-led sex education programs for and by persons with intellectual disabilities and/or autism - B. Nelson; M. Emmelin; A. Agardh; L. Löfgren; M. Stafström (Reproductive Health)
Abstract Background This study explored peer-led sex education for individuals with intellectual disabilities and/or autism (ID/ASD) from the perspective of project leaders within Swedish non-governmental organizations (NGOs). The purpose of this Grounded Theory study was to develop a conceptual model that characterizes the ways in which peer-led sex education is implemented by Swedish NGOs. This was done by exploring what the concept of peer-led sex education means to NGO project leaders, and how they experience, explain and reason about the application of peer education in their daily operations. Methods This study conducted 12 qualitative in-depth interviews with project leaders working with peer-led sex education initiatives. Grounded Theory enabled the construction of a conceptual model. Results The study identified the core category, "Shifting participatory approach when ideology meets reality," encapsulating project leaders’ experiences in managing peer-led sex education programs. Three distinct approaches were discerned: (1) The Radical approach, where project leaders prioritize empowerment and norm criticism, striving to create an inclusive and equitable environment for individuals with ID/ASD. This approach resonates with Paulo Freire's pedagogy of the oppressed, emphasizing liberation through education. (2) The Pragmatic approach, which navigates the tension between ideology and pragmatism, recognizing the co-dependency between project leaders and persons with ID/ASD. External pressures from funders and the requirements to achieve tangible project outcomes inform this approach. (3) The Skeptical approach, which exhibits caution, doubting the capabilities and willingness of individuals with ID/ASD to challenge societal norms and work equally with people without ID/ASD. Conclusions The findings underscore the complexity of peer-led sex education programs and highlight the need for a balanced approach that addresses both ideological aspirations and practical constraints. Empowerment and norm criticism are central to fostering agency and challenging oppressive systems. However, the pragmatic realities of project management and external pressures necessitate a delicate balance. Understanding these diverse approaches can inform the design of more effective initiatives, ultimately contributing to sexual and reproductive health and rights of individuals with ID/ASD.